On Solvability of the Matrix Equation AX – XB = C over Integer Rings - Prokip, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
In this communication we present conditions of solvability of Sylvester matrix equation AX – XB = C over integer domains. The necessary and sufficient conditions of solvability of Sylvester equation in term of columns equivalence of matrices constructed in a certain way by using the coefficients of this equation are proposed